Seasonal Performance Analysis of a Residential Heat Pump Using Different Fluids with Low Environmental Impact. (December 2015) - Botticella, Francesco; Viscito, Luca
Abstract: The growing of the energy consumption, in particular from buildings, both residential and commercial has induced a major interest for the analysis of the seasonal performance of heat pumps. The same considerations are effective for the well-known environmental problems related to direct and indirect emissions of carbon dioxide into the atmosphere and the incentives to support energy efficiency. In this work an air to water heat pump working with R290 and HFO1234yf has been modeled and simulated using the software package IMST-ART in order to evaluate the seasonal performance. Two different types of applications were considered: fan coils and radiant heat floor panels. Different types of building are considered. The seasonal performance in heating mode, SCOP, is calculated by coupling the performance of the heat pump in different operative conditions to a heating demand curve, in two different climate zones (average and colder). The results of the simulations show better performance of the heat pump with propane in both climates and applications, which is probably due to the state of current technology of the different components. In particular, the global performance of the compressor working with R1234yf is not yet optimized. At the same time a new design of the evaporator is desirable to reduce the pressure drops with R1234yf.